Proceedings of the Third International Scientific Medical Gathering Conference, Karbala, Iraq, 1–2 August 2025 - Mulazim Hussain Bukhari,; Ali Abed Saadoon AL Ghuzi,; Dhafir Fadel Hussein, (Journal of the Pakistan Medical Association, 2025)
The Third International Scientific Medical GatheringConference, held on August 1–2, 2025, in Karbala, Iraq,addressed health system preparedness and medicalchallenges during mass gatherings, with a particular focuson the Arbaeen pilgrimage. Organized by the ImamHussain Holy Shrine’s Health and Medical EducationBoard in partnership with the Popular MobilizationAuthority, the conference convened experts from Iraq,Iran, Russia, Pakistan, and other nations. The scientificprogramme featured keynote speeches, researchpresentations, and workshops covering clinical care,public health, administrative dimensions, and ethicalconsiderations . The proceedings advanced the field byexpanding the scope of topics to include cybersecurityand inclusive health services, emphasizing evidencebasedresearch, and moving towards integrated,actionable frameworks for operational readiness. Keyrecommendations included the development of nationalprotocols, real-time surveillance, and the expansion ofmobile medical services to ensure a safe pilgrimage. Keywords: Mass gathering medicine, Arbaeenpilgrimage, public health, disaster management, healthsystem preparedness.